The Hungarian touch a documentary on the Hungarian school of piano (Idéale Audience, 2002)
"One can immediately recognise pianists from the Hungarian school," says Zoltán Kocsis -- "as, before they've even placed their hands on the keyboard, they are given away by the way they hold themselves in front of the piano." A true representative of the Hungarian school and a great contemporary pianist, Zoltán Kocsis lets us into the secrets of his art, his teaching, and the tradition which he embodies for a whole generation of new pianists. His teaching serves to evoke the Major figures of the great Hungarian piano tradition, from Franz Liszt -- the first virtuoso pianist of modern times -- via Béla Bartók and Ernst von Dohnányi, to György Kurtag. Rare archival footage shows Annie Fischer and György Cziffra, two pianistic geniuses of the Hungarian piano school, in performance and Zoltán Kocsis aged 17, with his friends Andras Schiff and Dezsö Ranki being coached by an outstanding professor... Pál Kadosa